Classification of Rights and Freedoms of Human and Citizen in the Republic of Uzbekistan - Abdukadirov Sunnatilla Muzaffar Ugli; Achilova Lilia Ilkhomovna (Peerian Journals Publishing, 2023)
The rights of a person and a citizen can be classified on various grounds. "The rights of a citizen, given the peculiarities of this phenomenon, are already endowed by the state, and because of this, the state is free to take away and change such rights at its discretion, of course, on the basis of the Constitution and in accordance with it and other laws of the state. "Depending on the role of the state in their implementation, negative rights are distinguished, when the state must refrain from any actions in relation to the individual, and positive rights, when the state must ensure the realization of the right or assist in its protection."
Keywords: Human right; constitutional law; classification of rights and freedoms